Avaliação histológica da osseointegração de implantes dentários instalados em áreas de seio maxilar de humanos: uma revisão sistemática - Comassetto, Mateus Cassol (2024)
Rehabilitation with dental implants in the posterior maxilla is challenging due to frequent bone loss, especially in patients who have been edentulous for a long time or who have edentulism due to periodontitis, which necessitates bone volume augmentation. Histological analysis of the bone-implant interface is the most appropriate method for assessing bone consolidation around implants and understanding the factors that might influence this process. This is particularly relevant in critical areas with reduced bone volume and density, such as the maxillary sinus. Despite the existing clinical knowledge, there is a lack of comprehensive reviews in the scientific literature examining bone-implant integration histologically in cases where maxillary sinus floor augmentation (MSFA) has been performed. The aim of this study is to systematically evaluate the histological outcomes of bone-implant contact and bone density of dental implants placed in MSFA areas in humans. Studies were selected from electronic databases including MEDLINE (via PubMed), EMBASE, Cochrane Library, and grey literature. Randomized or controlled clinical trials and case series that assessed histological bone integration around implants placed in maxillary sinus areas were included. Randomeffects meta-analyses were performed to pool data on bone-implant contact (BIC%), bone density within the threads (BDWT%), and bone density outside the threads (BDOT%). Out of 1,788 potentially eligible articles, 11 studies were included, and 255 implants were analyzed. Most studies presented some concerns and serious risk of bias. The overall means for BIC, BDWT, and BDOT were 35.1% (95% CI: 28.0–42.1), 35.0% (95% CI: 24.6–45.3), and 37.4% (95% CI: 32.4–42.4), respectively. Subgroup analyses showed that late implants, with sandblasted and acid-etched surfaces (SLA), without loading, and associated a bone substitutes, had the highest BIC percentages (p < 0.05). Additionally, there was a significant increase in BIC at 2, 3-4, and beyond 4 months after implant installation. It can be concluded that different implant systems demonstrated potential for histological osseointegration in MSFA areas, although with significant variability. The observed differences between studies may be attributed to factors such as graft material type, timing of implant placement, implant surface, loading protocol, and healing period.